The impact of knowledge management in supporting innovation (a case study of the Libyan Oil Company in the Eastern Province) (Economic studies journal, 2020)
This study aims at identifying the effect of knowledge management on supporting innovation at Libya Oil Company through investigation on the relationship operations of Knowledge management (generating Knowledge, storing Knowledge, sharing Knowledge, and applying Knowledge) and innovation. The population of the study consists of all top and middle management directors at Libya Oil Company in the eastern area. The total number of the population reaches (105) participants. Due to unavailability of a number of the participants and refusal of the others to fill out the questionnaire form, the researcher reached (90) participants, among whom the questionnaire forms have been distributed. Only (75) questionnaire forms have been received valid for statistical analysis. The study has reached a set of findings. The most important of which are: there is a strong correlation between the independent variables(generating Knowledge, storing Knowledge, sharing Knowledge, and applying Knowledge) and innovation at Libya Oil Company. Also, it has been shown that there is in an effectual correlation of the independent variables (generating Knowledge, storing Knowledge, sharing Knowledge, and applying Knowledge) on innovation at Libya Oil Company. The study has recommended increasing of taking care of the operations of Knowledge management and taking care of the most prominent sources of Knowledge within the company represented in human resources as well as supporting and encouraging these human resources to innovation, creativity, sharing knowledge, and exchanging thoughts.
Keywords: Knowledge management; innovation; Libya Oil Company